2020
DOI: 10.3390/rs12172741
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Canopy Chlorophyll Content of Corn Based on Continuous Wavelet Transform Analysis

Abstract: The content of chlorophyll, an important substance for photosynthesis in plants, is an important index used to characterize the photosynthetic rate and nutrient grade of plants. The real-time rapid acquisition of crop chlorophyll content is of great significance for guiding fine management and differentiated fertilization in the field. This study used the method of continuous wavelet transform (CWT) to process the collected visible and near-infrared spectra of a corn canopy. This task was conducted to extract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…Hence, when we use Pearson correlation to analyze the relationship between the hyperspectral continuous wavelet coefficient and the chlorophyll content and water content of leaves, we find that there are many sensitive band regions of different degrees. Some recent study also confirmed that hyperspectral continuous wavelet coefficients are sensitive to changes in plant biochemical parameters [19,53,54]. Such a large number of sensitive bands extracted will affect the stability and accuracy of later modeling because it contains a large number of continuous bands.…”
Section: Model Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Hence, when we use Pearson correlation to analyze the relationship between the hyperspectral continuous wavelet coefficient and the chlorophyll content and water content of leaves, we find that there are many sensitive band regions of different degrees. Some recent study also confirmed that hyperspectral continuous wavelet coefficients are sensitive to changes in plant biochemical parameters [19,53,54]. Such a large number of sensitive bands extracted will affect the stability and accuracy of later modeling because it contains a large number of continuous bands.…”
Section: Model Resultsmentioning
confidence: 85%
“…They concluded that the relative moisture content of oak leaves and the absorption characteristic parameters exhibit linear relationships at 975 nm, 1200 nm, and 1750 nm, which indicates that hyperspectral can capture changes in moisture content. Zhang et al [19] used spectral continuous wavelet coefficients to estimate the chlorophyll content of corn pests, and the results confirmed the potential of hyperspectral inversion for determining chlorophyll content. Asner et al [20] developed a spectrum feature of Rapid Ohia Death (ROD) and found that 80% of plants infected with fungal pathogens had reduced water content and chlorophyll content.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Plant disease monitoring is of fundamental interest for crop management. Several studies related to different kinds of cultures have thus emerged, e.g., corn [1], wheat [2], grapes [3], or potatoes [4].…”
Section: Introduction 1contextmentioning
confidence: 99%
“…Three major problems of crop chlorophyll content analysis based on proximal spectroscopy methods include spectral signal-noise reduction, characteristic variable analysis, and analysis model establishment [13,14]. Among them, the noise reduction of spectral data is the primary step to improve the spectral data performance.…”
Section: Introductionmentioning
confidence: 99%